2012
DOI: 10.1002/nbm.2814
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of preimplantation embryo metabolism in human assisted reproductive techniques: a new biomarker for assessment of embryo implantation potential

Abstract: There has been growing interest in understanding energy metabolism in human embryos generated using assisted reproductive techniques (ART) for improving the overall success rate of the method. Using NMR spectroscopy as a noninvasive tool, we studied human embryo metabolism to identify specific biomarkers to assess the quality of embryos for their implantation potential. The study was based on estimation of pyruvate, lactate and alanine levels in the growth medium, ISM1, used in the culture of embryos. An NMR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 33 publications
(63 reference statements)
2
57
1
Order By: Relevance
“…In particular, our findings are contrary to the study of Seli et al, [26] and to the study of Pudakalakatti et al [18] where a positive correlation was found between implantation and NMR profiling. The reason for the difference is unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In particular, our findings are contrary to the study of Seli et al, [26] and to the study of Pudakalakatti et al [18] where a positive correlation was found between implantation and NMR profiling. The reason for the difference is unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study contrast several publications that showed a correlation between specific metabolic profiles of embryo spent culture media and successful implantation [18,[25][26][27][28]31,33]; however, our findings are consistent with the results from two recent randomized controlled trials [11,31,33] showing no improvement in pregnancy outcome when media profiling was added to the conventional embryo selection protocol. In particular, our findings are contrary to the study of Seli et al, [26] and to the study of Pudakalakatti et al [18] where a positive correlation was found between implantation and NMR profiling.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This can be a powerful means of assessing embryos that are viable from those that are not in the future. There are also growing evidence that metabolic profiles of spent embryo culture media differ between embryos that implant and those that fail to implant and may be used to predict reproductive potential [18][19][20][21]. Technologies that assess omic profiles are available, the problem is that they are commonly applied to assess individual pathway.…”
Section: Figurementioning
confidence: 99%